2019
DOI: 10.3389/fpsyg.2019.02269
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Alexithymia and Psychopathy in Heroin Dependent Individuals

Abstract: BackgroundPsychopathy and substance use disorders are highly co-morbid and their co-occurrence is associated with higher severity of addictive behavior and increased risk of violent offending. Both substance use disorders and psychopathy are related to prominent impairments in emotion processing, which are also central features of alexithymia. The nature of the relationship between psychopathy and alexithymia is not well-understood and has been particularly understudied among substance dependent individuals.Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 108 publications
1
8
0
1
Order By: Relevance
“…Consequently, the importance of considering alexithymia in the context of related constructs such as private self‐consciousness, emotion differentiation, and interoception is the potential value of this comparison for gaining greater insight into the nature of emotional processes and their relationship to AUD. Emotion‐focused interventions that improve emotion identification and differentiation skills may help moderate the influence of alexithymia and improve alcohol treatment outcomes, which is consistent with recent appeals to address the ability to attend to internal states as a target of clinical interventions (Psederska et al, 2019; Swan et al, 2020). Emotion regulation treatment for AUD, dialectical behavior therapy, and cognitive‐behavioral therapy for depression address emotion regulation deficits and may provide information on treatment content that could be adapted to supplement AUD treatment (Asnaani et al, 2020; Cavicchioli et al, 2020; Stasiewicz et al, 2018; Strauss et al, 2019).…”
Section: Discussionsupporting
confidence: 68%
“…Consequently, the importance of considering alexithymia in the context of related constructs such as private self‐consciousness, emotion differentiation, and interoception is the potential value of this comparison for gaining greater insight into the nature of emotional processes and their relationship to AUD. Emotion‐focused interventions that improve emotion identification and differentiation skills may help moderate the influence of alexithymia and improve alcohol treatment outcomes, which is consistent with recent appeals to address the ability to attend to internal states as a target of clinical interventions (Psederska et al, 2019; Swan et al, 2020). Emotion regulation treatment for AUD, dialectical behavior therapy, and cognitive‐behavioral therapy for depression address emotion regulation deficits and may provide information on treatment content that could be adapted to supplement AUD treatment (Asnaani et al, 2020; Cavicchioli et al, 2020; Stasiewicz et al, 2018; Strauss et al, 2019).…”
Section: Discussionsupporting
confidence: 68%
“…The relationship between alexithymia and addictions has been documented and discussed many times, including in such fields as heroin dependent [ 44 ], alcohol addiction [ 20 ], internet addiction [ 9 ], pathological gambling [ 45 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of drug use reflects a degree of craving, and patients with high subjective cravings will repeatedly self-administer drugs. One study on alcohol consumption found that alexithymia is associated with subjective hypersensitivity to bodily sensations, and difficulty identifying feelings mediated the relationship between sensitivity to bodily sensations and alcohol consumption [ 44 ]. Consistent with our research, one study tested cue-elicited craving responses in methamphetamine-dependent individuals and found a positive correlation between the difficulty identifying feelings and cue-elicited craving responses [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…People with addictive disorders have been already characterized as more prone to alexithymia than controls, even when evaluated after a prolonged period of abstinence [ 59 ]. However, no distinction between different addictive disorders had been made.…”
Section: Discussionmentioning
confidence: 99%